Algorithms, AI and music composition: When can musical creativity be considered pop? - Allegra, Serena (Scenari, 2024)
Traditional musicology has long considered pop music and classical music as two distinct entities, or even as two ontologically opposed categories, each with specific aesthetic, structural and compositional characteristics. The recent development of Artificial Intelligence (AI), in parallel with the use of learning algorithms, has prompted some reflection on the type of creativity associated with their use. In particular, the use of AI in the compositional phase is generally associated with popular music rather than classical music. However, if a convergence could be observed in this very compositional approach, it would mean that both musical domains, albeit with different results, originate from the same creative act: this could lead to a less rigid boundary between them. In fact, if one considers that musical creativity (both classical and pop) is the result of human beings’ ability to extend themselves beyond the boundaries of the skin through the technologies they produce, the presumed hierarchical superiority or inferiority of one of the two musical domains over the other becomes insubstantial. The aim, therefore, is to question the hierarchical dichotomy between popular and classical music, starting with a critical examination of compositional approaches and proceeding to the analysis of illustrative cases identified on a diachronic level. These cases show that the human tendency to delegate certain cognitive processes to more or less complex technologies is not a recent phenomenon, even in the field of music. A reassessment of the phenomenon is therefore proposed that goes beyond its external outcomes.